Recent Advances in Alternative Medicine (IntechOpen, 2024)
Modern medicine tends to favor treatment with pharmaceuticals. However, there is a growing trend towards personalized and holistic medicine that incorporates a person’s biopsychosocial and spiritual perspective. This book discusses some of these alternative medical approaches, including biofeedback vibrational medicine, acupuncture, and more. Health and wellness must be redefined, and lifestyle should be taken into consideration without ignoring traditional and alternative medical methods. This book presents a comprehensive overview of alternative medicine, presenting new approaches to health in combination with modern orthodox medicine.